Chapter 12 Genesis of state space Frontier commodification in Malaysian Borneo - Ishikawa, Noboru (Taylor & Francis, 2018)
"In Asia, where authoritarian-developmental states have proliferated, statehood and social control are heavily contested in borderland spaces. As a result, in the post-Cold War world, borders have not only redefined Asian incomes and mobilities, they have also rekindled neighbouring relations and raised questions about citizenship and security. The contributors to the Routledge Handbook of Asian Borderlands highlight some of these processes taking place at the fringe of the state. Offering an array of comparative perspectives of Asian borders and borderlands in the global context, this handbook is divided into thematic sections, including: •Livelihoods, commodities and mobilities •Physical land use and agrarian transformations •Borders and boundaries of the state and the notion of statelessness •Re-conceptualizing trade and the economy in the borderlands •The existence and influence of humanitarians, religions, and NGOs •The militarization of borderlands Causing us to rethink and fundamentally question some of the categories of state, nation, and the economy, this is an important resource for students and scholars of Asian Studies, Border Studies, Social and Cultural Studies, and Anthropology."